An IoT-based intelligent traffic engagement system with emergency vehicles pre-emption. (26th August 2022) - Pant, Bharat; Sharma, Harsh; Chawla, Rashmi; Kumar, Chirag
The increase in vehicles beyond the handling capacity of transport infrastructure leads to congestion-like situations. As a consequence, vehicles experience extended waiting time on roads and a severe impact on emergency services. The existing works are either focused on normal traffic management or handling emergency situations. This manuscript aims to provide a complete solution to address these tasks. The proposed system updates the timer dynamically using Kullback-Leibler (KL) divergence to measure the traffic density to handle the normal traffic. In the case of emergency vehicles (EV), the system is added with EV pre-emption. Finally, the system has the capability to handle multiple EVs appearing simultaneously in different lanes. For the efficacy of the proposed system, multiple experiments and comparisons with state-of-the-art techniques are carried out using the simulation of urban mobility (SUMO) traffic simulator.